Therapeutic Effects of Dipterocarpus tuberculatus with High Antioxidative Activity Against UV-Induced Photoaging of NHDF Cells and Nude Mice - Su Jin Lee; Ji Eun Kim; Yun Ju Choi; Jeong Eun Gong; So Hae Park; Bounleuane Douangdeuane; Onevilay Souliya; Ju Min Park; Hee Seob Lee; Bae-Hwan Kim; Dae Youn Hwang (Antioxidants, 2021)
To investigate the therapeutic effects of methanol extracts of Dipterocarpus tuberculatus Roxb. (MED) against UV-induced photoaging, we assessed for alterations in the antioxidant activity, anti-apoptotic effects, ECM modulation, skin appearances, and anti-inflammatory response in normal human dermal fibroblast (NHDF) cells and nude mice orally treated with MED. High levels of tannin content and high free radical scavenging activity to DPPH were determined in MED, while seven active components, namely, gallic acid, bergenin, ellagic acid, ε-viniferin, asiatic acid, oleanolic acid, and 2α-hydroxyursolic acid, were identified using LC–MS analyses. UV-induced alterations in the NO concentration, SOD activity, and Nrf2 expression were remarkably recovered in MED-treated NHDF cells. Moreover, the decreased number of apoptotic cells and G2/M phase arrest were observed in the UV + MED-treated groups. Similar recoveries were detected for β-galactosidase, MMP-2/9 expression, and intracellular elastase activity. Furthermore, MED treatment induced suppression of the COX-2-induced iNOS mediated pathway, expression of inflammatory cytokines, and inflammasome activation in UV-radiated NHDF cells. The anti-photoaging effects observed in NHDF cells were subsequently evaluated and validated in UV + MED-treated nude mice through skin phenotypes and histopathological structure analyses. Taken together, these results indicate that MED exerts therapeutic effects against UV-induced photoaging and has the potential for future development as a treatment for photoaging.